Functional trialkoxysilane mediated controlled synthesis of fluorescent gold nanoparticles and fluoremetric sensing of dopamine - Mitra M.D.; Pandey P.C. (My University, 2025)
We report herein the synthesis of fluorescent gold nanoparticles (AuNPs) involving the active role of 3-aminopropyltrimethoxysilane (3-APTMS) and 3-glycidoxypropyltrimethoxysilane (3-GPTMS) as active reducing and stabilizing agents. As made, AuNPs showed excellent fluorescent activity with QY∼13%, and the blue fluorescence of nanoparticles is confirmed by CIE Coordinates. The fluorescent AuNPs were characterized by X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM), zeta potential, UV–Visible spectroscopy, X-ray diffraction (XRD), fluorescence spectroscopy (FL), and Edinburgh Instrument. Interestingly, the synthesized fluorescent AuNPs with an average size of 4–10 nm was successfully used as a selective nanoprobe based on fluorescence quenching for the sensing of dopamine (DA). The mechanism of the AuNPs were associated via the electron transfer process. The limit of detection for DA is found to be 0.63 nM with a linear range of 0.05–0.6 mM (R2 = 0.998). Furthermore, the sensing of DA was also investigated in a real sample (CSF) and was found to have good accuracy and recovery, justifying sensitive, selective, and cost-effective techniques for the detection of dopamine in real samples. © 2022 Elsevier B.V.